Carbon nanotube-containing powder for electrodes of power storage device, electrode mixture paste, electrodes for power storage device, and power storage device
The use of ethyl cellulose as a dispersant for CNTs in a CNT-containing powder improves dispersibility and conductivity in power storage devices, addressing aggregation issues and enhancing electrode performance.
Patent Information
- Application Number
- JP2023114709
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
AI Technical Summary
Carbon nanotubes (CNTs) tend to aggregate and are difficult to disperse effectively in electrode active materials, leading to insufficient conductivity in power storage devices, resulting in high volume resistivity.
A CNT-containing powder is formulated with ethyl cellulose as a dispersant, achieving a weight ratio of 33:67 to 99:1, which is kneaded and dried to form a paste-like product, ensuring the dispersant adheres to the CNT surface, enhancing dispersibility and conductivity.
The CNT-containing powder exhibits excellent dispersibility and conductivity, reducing volume resistivity in electrodes, thereby improving discharge capacity of power storage devices.
Smart Images

Figure 2025012119000003 
Figure 2025012119000004 
Figure 2025012119000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a carbon nanotube (CNT)-containing powder for an electrode of an electricity storage device, a manufacturing method thereof, an electrode mixture paste containing the CNT-containing powder for an electrode, an electrode for an electricity storage device including an electrode mixture layer manufactured using the electrode mixture paste, and an electricity storage device. [Background technology]
[0002] Carbon nanotubes (hereinafter sometimes referred to as "CNTs") have been known as materials with excellent properties such as electrical conductivity, thermal conductivity, and mechanical properties. In recent years, the positive electrode of a lithium-ion secondary battery is made up of three main materials: an electrode active material, a binder, and a conductive additive. Of these, the active material, which accounts for more than 90% of the positive electrode mixture, has poor electrical conductivity. To solve this problem, carbon black (acetylene black) has been used as a conductive additive. However, in recent years, CNTs, which have better electrical conductivity than carbon black, have been attracting attention.
[0003] For CNTs to function effectively as a conductive assistant, they must be sufficiently dispersed in the electrode active material. However, since CNTs tend to aggregate and are difficult to disperse, attempts have been made to improve their dispersibility by preparing a CNT dispersion containing CNTs and a dispersant in advance and mixing it with the electrode active material, etc. For example, Patent Document 1 discloses a carbon nanotube dispersion containing a carbon nanotube-containing composition, a cellulose derivative having a structural unit represented by general formula (1), and an organic solvent, the organic solvent containing at least one selected from aprotic polar solvents and terpenes, the concentration of the carbon nanotube-containing composition contained in the carbon nanotube dispersion is 1% by mass or less, and when the dispersion is centrifuged at 10,000 G for 10 minutes and 90 vol% is collected as the supernatant, the concentration of the carbon nanotube dispersion in the supernatant is 80% or more of the concentration of the carbon nanotube dispersion before the centrifugation. Patent Document 2 describes a method for producing a dispersion system in which carbon fibers and a dispersing agent that is solid at least at room temperature (20±10°C) are added to an aqueous dispersion medium, and the carbon fibers are isolated and dispersed in the dispersion medium. The method comprises removing the dispersion medium from the dispersion system, and the carbon fibers are aggregated and solidified while maintaining their independent dispersion. The document describes a redispersible fine carbon fiber agglomerate, which has a fine carbon fiber content of 0.01 to 99.5% by mass, a dispersant content of 0.1 to 99.5% by mass, and a water content of less than 10% by mass, and is characterized in that the dispersant is any one selected from (1) a surfactant capable of forming spherical, rod-like, or plate-like micelles having a diameter of 5 to 2,000 nm in an aqueous solution, (2) a water-soluble polymer having a weight-average molecular weight of 10,000 to 50,000,000, and (3) a combination of cyclodextrin and fullerene. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 188175 [Patent Document 2] JP 2008-274502 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, when the inventors prepared an electrode mixture paste for an electricity storage device from the carbon nanotube dispersion liquid described in Patent Document 1 and observed the surface condition of the electrode active material using an electron microscope, they found that the CNTs had aggregated and were insufficiently dispersed in some areas.In addition, when they prepared an electrode for an electricity storage device and examined its conductivity, they found that the volume resistivity was not sufficiently low, leaving room for improvement. In addition, the redispersible fine carbon fiber agglomerate described in Patent Document 2 was prepared, and an electrode mixture paste for an electricity storage device was prepared from the agglomerate to examine the conductivity of the electrode for an electricity storage device. As a result, it was found that the volume resistivity was also not sufficiently low, leaving room for improvement.
[0006] Therefore, an object of the present invention is to provide a carbon nanotube (CNT)-containing powder for an electrode of an electricity storage device, which can exhibit excellent dispersibility in an electrode mixture of the electricity storage device, and a method for producing the same. Another object of the present invention is to provide an electrode composite for an electricity storage device, which can obtain an electrode for an electricity storage device having a low volume resistivity by using the CNT-containing powder for an electrode, and an electrode for an electricity storage device and an electricity storage device using the electrode mixture paste. [Means for solving the problem]
[0007] The present invention relates to carbon nanotubes (CNTs) and With ethyl cellulose as a dispersant The present invention relates to a CNT-containing powder for an electrode of an electricity storage device, comprising:
[0008] In an embodiment of the present invention, the dispersant may be attached to the surface of the CNT.
[0009] In an embodiment of the present invention, the weight ratio of the content of the CNT to the content of the dispersant (CNT:dispersant) may be 33:67 to 99:1.
[0010] Another embodiment of the present invention relates to an electrode composite for an electricity storage device, comprising the CNT-containing powder for an electrode and an inorganic compound, wherein the inorganic compound is an electrode active material and / or a solid electrolyte.
[0011] In another embodiment of the present invention, the present invention relates to an electrode mixture paste for an electricity storage device, which contains the CNT-containing powder for an electrode of an electricity storage device, an electrode active material, a binder, and a solvent.
[0012] In another embodiment, the present invention relates to an electrode for an electricity storage device, comprising an electrode mixture layer formed using the electrode mixture paste for an electricity storage device.
[0013] In another embodiment, the present invention relates to an electricity storage device including an electrode mixture layer formed using the electrode mixture paste for an electricity storage device.
[0014] In another embodiment of the present invention, there is provided a method for producing a CNT-containing powder for an electrode of an electric storage device, comprising the steps of: The present invention relates to a method for producing a paste-like kneaded product by kneading CNTs, a dispersant, and a solvent, and then drying the kneaded product to obtain a CNT-containing powder.
[0015] In the other embodiment, the solvent may be one or more selected from the group consisting of alcohol-based solvents, amine-based solvents, ether-based solvents, glycol ester-based solvents, and ketone-based solvents. Effect of the Invention
[0016] Since the CNT-containing powder for an electrode of an electricity storage device of the present invention has excellent dispersibility in an electrode for an electricity storage device and can obtain excellent electrical conductivity, an electrode for an electricity storage device obtained by using an electrode composite or an electrode mixture paste containing the CNT-containing powder for an electrode has a low volume resistivity and excellent electrical conductivity. Therefore, an electricity storage device obtained by using the CNT-containing powder for an electrode of an electricity storage device of the present invention can remarkably improve the discharge capacity. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 shows an electron microscope image (a) (×5,000 magnification) of the surface of an electrode prepared using the electrode mixture paste 1 obtained in Example 14, and an enlarged electron microscope image (b) (×50,000 magnification). [Diagram 2] FIG. 2 shows an electron microscope image (a) (×5,000 magnification) of the surface of an electrode prepared using the electrode mixture paste 19 obtained in Comparative Example 12, and an enlarged electron microscope image (b) (×50,000 magnification). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described.
[0019] <CNT-containing powder for electrodes of electricity storage devices> The CNT-containing powder for an electrode of an electricity storage device according to an embodiment of the present invention (hereinafter also referred to as the CNT powder of the present invention or the CNT powder for an electrode) is characterized by containing carbon nanotubes (CNTs) and ethyl cellulose as a dispersant.
[0020] Examples of CNTs used in the present invention include single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). The SWCNTs and MWCNTs may be any that can be used in an electrode for an electricity storage device, and there are no particular limitations on, for example, the diameter, length and aspect ratio of the SWCNTs or MWCNTs. In the present invention, SWCNTs and MWCNTs may be used alone or in combination.
[0021] The ethyl cellulose used as a dispersant in the present invention is a water-insoluble cellulose ether in which some and / or all of the three hydroxyl groups of cellulose are substituted with ethyl groups.
[0022] The weight average molecular weight (Mw) of the ethyl cellulose is preferably from 20,000 to 300,000, and more preferably from 30,000 to 200,000, from the viewpoints of solubility in a solvent and dispersibility of CNTs. As the ethyl cellulose, commercially available products can be used, such as ETHOCEL (registered trademark) series manufactured by Dow Chemical Company and Aqualon (registered trademark) manufactured by Ashland Chemical Company. TM Examples include the ethylcellulose series.
[0023] In the CNT powder of the present invention, the weight ratio of the CNTs to the dispersant (CNT:dispersant) may be adjusted to within a range of 33:67 to 99:1, and is more preferably adjusted to within a range of 40:60 to 80:20.
[0024] The CNT powder of the present invention can be produced by kneading the CNTs, the dispersant and a solvent to produce a paste-like kneaded mixture, and then drying the kneaded mixture.
[0025] In addition, the CNT powder of the present invention has a structure in which the dispersant is attached to the surface of the CNTs. With such a structure, the CNT powder of the present invention has excellent dispersibility in an electrode material and can be attached widely to the surface of electrode materials such as electrode active materials and solid electrolytes, thereby exhibiting excellent electrical conductivity. The presence of the above structure can be confirmed, for example, by dispersing the CNT powder of the present invention in a solvent such as N-methyl-2-pyrrolidone (NMP) and examining the weight of the dispersant released. If the weight of the released dispersant is less than 10% of the weight of the dispersant contained in the CNT powder, it can be determined that the CNT powder has the above structure.
[0026] Commercially available and conventional products (dispersions) have the following disadvantages: 1. In general, dispersions are known to be less stable and have a shorter product lifespan than the CNT powder of the present invention because they are more susceptible to rheological changes due to CNT aggregation and precipitation, and concentration changes due to solvent evaporation. 2. Because the product life is short, and in order to reuse the solvent recovered and regenerated at the battery factory at the dispersion factory, it is necessary to build a dispersion factory near the battery factory. 3. The CNT content of commercially available products is generally 6% by weight or less. Such a low CNT content places limitations on the formulation of the electrode mixture. 4. The low CNT content and large volume and weight (per unit weight of CNT) result in high transportation and storage costs. 5. Dispersion design is required to suit the battery system. For example, different solvents can be used for liquid lithium-ion batteries and sulfide-based solid-state batteries. If the solvent changes, it is highly likely that the CNT dispersion conditions will also change.
[0027] The CNT powder of the present invention has the following advantages: 1. It has good stability, such as no change in rheology due to aggregation or precipitation of CNTs, or no change in concentration due to solvent volatilization. 2. The product has a long lifespan, and since the solvent recovered and regenerated at the battery factory is not reused at the dispersion factory, there is no need to build a dispersion factory near the battery factory. 3. Because the CNT content is high, there are virtually no restrictions on the formulation when preparing the electrode mixture. 4. The CNT content is high and the volume and weight (per unit weight of CNT) are small, so transportation and storage costs are low. 5. Because it has excellent dispersibility when used to prepare electrode mixtures of various compositions, it can be applied to various battery systems. For example, the same CNT powder can be used in liquid lithium-ion batteries and sulfide-based all-solid-state batteries.
[0028] Examples of the solvent include alcohol-based solvents, amine-based solvents, ether-based solvents, glycol ester-based solvents, and ketone-based solvents. Examples of the alcohol solvent include methanol, ethanol, normal propyl alcohol, isopropyl alcohol (IPA), butyl alcohol, octyl alcohol, cyclohexanol, allyl alcohol, benzyl alcohol, cresol, furfuryl alcohol, propylene glycol monomethyl ether (PM), ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol tertiary butyl ether (ETB), ethylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol monopropyl ether, ethylene glycol phenyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, and dipropylene glycol monomethyl ether. Examples of the amine solvent include N,N-dimethylaminopropylamine and diethylenetriamine. Examples of the ether solvent include methyl phenyl ether (anisole), tetrahydrofuran, dioxane, and ethylene glycol dimethyl ether. Examples of the glycol ester solvent include propylene glycol monomethyl ether acetate (PMA), ethylene glycol monoethyl ether acetate, 3-methoxybutyl acetate, and ethylene glycol diacetate. Examples of the ketone solvent include acetone, methyl ethyl ketone (MEK), cyclopentanone, and cyclohexanone. The above solvents can be used alone or in combination of two or more kinds.
[0029] The amount of the solvent to be mixed with the CNTs and the dispersant is not particularly limited as long as a paste-like kneaded product can be obtained.
[0030] Examples of the mixer used for the kneading include a planetary mixer, a kneader, an extrusion type kneader, and a thin film rotary type high speed agitator. The planetary mixer is a machine that mixes materials by using the centrifugal force generated by rotating and revolving (planetary motion) to retain materials and create shear stress, and is also called a planetary mixer. The planetary stirrer is not particularly limited and may be a commercially available manufacturing device.
[0031] The conditions for preparing the kneaded material are not particularly limited. As for the temperature, the kneading is preferably performed at a temperature lower than the boiling point of the solvent.
[0032] The means for drying the kneaded material obtained as described above is not particularly limited, and may be an apparatus capable of adjusting the temperature to a temperature equal to or higher than the temperature at which the solvent volatilizes, an apparatus capable of removing the solvent by reducing pressure, a freeze-drying apparatus, etc. For example, from the viewpoint of efficient drying, it is preferable to increase the processing temperature in the planetary agitator to volatilize the solvent while kneading the kneaded material.
[0033] The degree of volatilization of the solvent is not particularly limited as long as the kneaded material is in a powder form. If the kneaded material is not sufficiently dried or has an odor of the solvent when taken out of the drying device, additional drying may be performed. The CNT powder of the present invention has a property of being less likely to aggregate even in such a drying process.
[0034] <Electrode composite for power storage devices> The electrode composite of the present invention (hereinafter also referred to as the electrode composite) for an electricity storage device contains the CNT powder for an electrode and an inorganic compound, and is characterized in that the inorganic compound is an electrode active material and / or a solid electrolyte.
[0035] The electrode composite can be used as a material for producing an electrode for an electricity storage device. For example, the electrode composite containing the electrode active material is mixed with carbon black, a binder and a solvent, and kneaded to produce an electrode mixture paste for an electricity storage device.
[0036] The inorganic compound includes an electrode active material and a solid electrolyte.
[0037] The electrode active material includes active materials used for either the positive electrode or the negative electrode. The positive electrode active material is, for example, a layered oxide (LiCoO2, LiNiO2, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 etc.), spinel oxides (LiMnO2, LiMn 1.6 Ni 0.4 O4, etc.), olivine type oxides (LiFePO4, Fe2(SO4)3, LiCoPO4, etc.), inverse spinel type oxides (LiCoVO4, LiNiVO4, etc.), etc. Examples of the negative electrode active material include carbonaceous materials (graphite, non-graphitizable carbon, amorphous carbon, polymer compound sintered bodies (e.g., phenolic resin, furan resin, etc., sintered and carbonized), cokes (e.g., pitch coke, needle coke, petroleum coke, etc.), carbon fibers, etc.) and oxides (Li2TiO3, TiNb x O, etc.), silicon-based (Si, SiO, etc.), etc. The positive electrode active material and the negative electrode active material may each be used alone or in combination of two or more kinds.
[0038] The solid electrolyte is a solid that can conduct only ions, and may be any electrolyte that can be used in a power storage device according to the type of the power storage device described below. For example, the following can be given as a lithium ion conductive solid electrolyte: ·Oxide-based solid electrolyte: Crystalline (Li 1.3 Al 0.3 Ti 1.7 (PO4)3, La 0.51 Li 0.34 TiO 2.94 , Li7La3Zr2O 12 etc.), amorphous (Li 2.9 PO 3.3 N 0.46 etc.) ·Sulfide-based solid electrolyte: Crystalline (Li 10 GeP2S 12 , Li 3.25 Ge 0.25 P 0.75 S4, Li6PS5Cl, etc.), glass ceramics (Li7P3S 11 etc.), amorphous (70Li2S-30P2S5 etc.) Other (Li2B 12 H 12 , Li3OCl 0.5 Br 0.5 etc.)
[0039] The content of the CNT-containing powder of the present invention in the electrode composite is not particularly limited, and may be appropriately adjusted depending on the type of inorganic compound, the type of CNT, the type of electrode to be applied, and the type of electricity storage device to be applied. For example, in the case of a composite used for the negative electrode of a secondary battery, the content of the CNT-containing powder may be 0.01 to 10% by weight.
[0040] The electrode composite can be produced by mixing the CNT-containing powder for an electrode with the inorganic compound.
[0041] The mixing method is not particularly limited, and may be either a wet method or a dry method. Examples of the mixer used for the mixing include a planetary mixer, a kneader, an extrusion type kneader, and a thin film rotary type high-speed mixer.
[0042] For example, an electrode composite containing an electrode active material as an inorganic compound can be produced by the following steps. Homogenization step: A mixture of the electrode active material, CNT powder for the electrode, and a solvent is prepared. Fiber defibration step: The mixture is kneaded using the mixer. Finishing process: If necessary, the solvent is removed by drying or the like.
[0043] The solvent is not particularly limited, and examples of the solvent include alcohol solvents such as methanol, ethanol, normal propyl alcohol, IPA, butyl alcohol, octyl alcohol, cyclohexanol, allyl alcohol, benzyl alcohol, cresol, and furfuryl alcohol; Alcohol ether solvents such as PM, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ETB, ethylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol monopropyl ether, ethylene glycol phenyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, and dipropylene glycol monomethyl ether; Amine solvents such as N,N-dimethylaminopropylamine and diethylenetriamine, Ether solvents such as methyl phenyl ether, tetrahydrofuran, dioxane, and ethylene glycol dimethyl ether; Glycol ester solvents such as PMA, ethylene glycol monoethyl ether acetate, 3-methoxybutyl acetate, and ethylene glycol diacetate; Ketone solvents such as acetone, MEK, cyclopentanone, and cyclohexanone, Aromatic hydrocarbon solvents such as benzene, toluene, xylene, cymene, and mesitylene, Aprotic polar solvents such as NMP, dimethylsulfoxide, and dimethylformamide, Aliphatic hydrocarbon solvents such as pentane, normal hexane, octane, cyclopentane, and cyclohexane; Aldehyde solvents such as furfural, Ester solvents such as butyl acetate, ethyl acetate, methyl acetate, butyl propionate, ethylene glycol monoethyl ether acetate, 3-methoxybutyl acetate, ethylene glycol diacetate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, and butyl butyrate; Polyol solvents such as glycerol, ethylene glycol, and diethylene glycol, etc. Among these, when NMP is used, good defibrillation properties of CNTs can be achieved.
[0044] In the defibration step, the concentration of the electrode active material is adjusted to the tap density (D Tap ) (unit: g / cm 3 ) to the concentration (C) (unit: weight %) of the electrode active material calculated based on the following formula (1), the defibrillation property of the CNTs when kneaded with the solvent can be improved, and the uniform dispersion of the CNTs can be improved.
[0045] C=7.0×D Tap +α...Formula (1) (In the formula, 60≦α≦70.)
[0046] The tap density of the electrode active material can be measured according to a recipe in accordance with JIS K 5101-12-2. For commercially available electrode active materials, the values listed in the catalogs may be used.
[0047] <Electrode mixture paste for power storage devices> The electrode mixture paste for an electricity storage device of the present invention (hereinafter also referred to as the electrode mixture paste of the present invention) contains the CNT powder for an electrode, an electrode active material, a binder, and a solvent.
[0048] The content of the CNT powder for electrodes in the electrode mixture paste of the present invention may be adjusted as appropriate according to the type of electricity storage device to which it is applied, from the viewpoints of improving electrical conductivity and the capacity of the electricity storage device.
[0049] The electrode active material is not particularly limited as long as it can be used in the electrode composite.
[0050] The content of the electrode active material in the electrode mixture paste of the present invention may be appropriately adjusted according to the type of the applied electricity storage device from the viewpoint of improving the electrical conductivity and the capacity of the electricity storage device.
[0051] The binder may be any binder that can be used in an electrode for a power storage device, and examples thereof include polyvinylidene fluoride (PVDF), polyvinyl alcohol, polyvinyl acetal, acrylic resin, polyvinyl acetate, polyvinyl chloride, polystyrene, polyvinyl ether, polyvinylpyrrolidone (PVP), styrene butadiene rubber (SBR), and carboxymethyl cellulose. These may be modified with various functional groups, and polar functional groups such as acidic groups and basic groups can be suitably used as the functional groups. The binders may be used alone or in combination of two or more.
[0052] The weight average molecular weight of the binder is not particularly limited, but for example, one within the range of 110,000 to 5,000,000 can be suitably used.
[0053] The content of the binder in the electrode mixture paste of the present invention may be appropriately adjusted according to the type of the applied electricity storage device from the viewpoint of improving the electrical conductivity and the capacity of the electricity storage device.
[0054] The solvent is not particularly limited, and examples of the solvent include alcohol solvents such as methanol, ethanol, normal propyl alcohol, IPA, butyl alcohol, octyl alcohol, cyclohexanol, allyl alcohol, benzyl alcohol, cresol, and furfuryl alcohol; Alcohol ether solvents such as PM, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ETB, ethylene glycol monobutyl ether, 3-methoxy-3-methyl-1-butanol, ethylene glycol monopropyl ether, ethylene glycol phenyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, and dipropylene glycol monomethyl ether; Amine solvents such as N,N-dimethylaminopropylamine and diethylenetriamine, Ether solvents such as methyl phenyl ether, tetrahydrofuran, dioxane, and ethylene glycol dimethyl ether; Glycol ester solvents such as PMA, ethylene glycol monoethyl ether acetate, 3-methoxybutyl acetate, and ethylene glycol diacetate; Ketone solvents such as acetone, MEK, cyclopentanone, and cyclohexanone, Aromatic hydrocarbon solvents such as benzene, toluene, xylene, cymene, and mesitylene, Aprotic polar solvents such as NMP, dimethylsulfoxide, and dimethylformamide, Aliphatic hydrocarbon solvents such as pentane, normal hexane, octane, cyclopentane, and cyclohexane; Aldehyde solvents such as furfural, Ester solvents such as butyl acetate, ethyl acetate, methyl acetate, butyl propionate, ethylene glycol monoethyl ether acetate, 3-methoxybutyl acetate, ethylene glycol diacetate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, and butyl butyrate; Polyol solvents such as glycerol, ethylene glycol, and diethylene glycol, etc. Among these, when NMP is used, good defibrillation properties of CNTs can be achieved.
[0055] The electrode mixture paste of the present invention is obtained by kneading the CNT powder for electrodes, the electrode active material, the binder, and the solvent. The kneading method is not particularly limited, but examples of the mixer used for kneading include a planetary mixer, a kneader, an extrusion type kneader, and a thin film rotary type high-speed mixer.
[0056] In terms of the mixing order, each component may be mixed simultaneously, or the CNT powder for an electrode, the electrode active material, and the binder may be mixed in that order into the solvent. This order is not particularly limited, and the mixture of the CNT powder for an electrode and the electrode active material (electrode composite) may be added gradually. Also, the solvent and the binder may be mixed and dissolved in advance.
[0057] The ratio of the electrode components in the electrode mixture paste, i.e., the ratio of the CNT powder for an electrode, the electrode active material, and the binder in the electrode mixture paste, may be appropriately adjusted according to the type of electricity storage device to be applied, from the viewpoints of the thickness and coatability of the resulting electrode.
[0058] The electrode mixture paste of the present invention can be prepared, for example, by the following steps. Homogenization step: A mixture of the electrode active material, CNT powder for the electrode, and a solvent is prepared. Fiber defibration step: The mixture is kneaded using the mixer. Finishing step: adding binder and, if necessary, solvent.
[0059] In the defibration step, the concentration of the electrode active material is adjusted to the tap density (D Tap ) (unit: g / cm 3 ) to the concentration (C) (unit: weight %) of the electrode active material calculated based on the above formula (1), the defibrillation property of the CNTs when kneaded with the solvent can be improved, and the uniform dispersion of the CNTs can be improved.
[0060] The tap density of the electrode active material can be measured according to a recipe in accordance with JIS K 5101-12-2. For commercially available electrode active materials, the values listed in the catalogs may be used.
[0061] <Electrodes for electricity storage devices> The electrode for a power storage device of the present invention (hereinafter also referred to as the electrode of the present invention) includes an electrode mixture layer formed using the electrode mixture paste of the present invention, and specifically, is obtained by applying the electrode mixture paste of the present invention to a current collector and drying the obtained product. By the drying, the solvent in the electrode mixture paste of the present invention is removed, and an electrode mixture layer is formed on the current collector, thereby obtaining an electrode.
[0062] In the electrode of the present invention, the current collector may be made of Al, Ni, Cu, stainless steel or the like. Examples of the shape of the current collector include foil, plate, mesh, net, lath, punched metal, embossed, and combinations of these (e.g., mesh-like plate, etc.) The surface of the current collector may be unevenly etched.
[0063] The method for applying the electrode mixture paste of the present invention to the current collector is not particularly limited. Examples of the method include slit die coating, screen coating, curtain coating, knife coating, gravure coating, and electrostatic spraying. Drying after coating may be performed by heat treatment, air drying, vacuum drying, or the like. When drying is performed by heat treatment, the temperature is usually about 50 to 150°C. Pressing may be performed after drying. Examples of the pressing method include die pressing and roll pressing. The electrode of the present invention can be manufactured by the above-mentioned method. The thickness of the electrode is usually about 5 to 500 μm.
[0064] <Electricity storage device> The electricity storage device of the present invention includes an electrode mixture layer formed using the electrode mixture paste of the present invention.Specific examples of the electricity storage device include a liquid-type or solid-type electricity storage device including the electrode of the present invention on which an electrode mixture layer made of the electrode mixture paste of the present invention is formed. Examples of such energy storage devices include liquid-type energy storage devices (lithium ion batteries, sodium ion batteries, polyvalent metal ion batteries, lithium-sulfur batteries, sulfide batteries, conversion batteries, redox flow batteries, fluoride batteries, chloride batteries, zinc negative electrode batteries, etc.), various all-solid-state batteries (sulfide-based, oxide-based, nitride-based, polymer-based, etc.), various air batteries (lithium-air batteries, zinc-air batteries, sodium-air batteries, etc.), various capacitors (lithium ion capacitors, electric double layer capacitors, etc.), and various fuel cells (solid polymer type, alkaline type, etc.).
[0065] The electric storage device of the present invention can be manufactured by a known method for manufacturing an electric storage device, except for using the electrode of the present invention. The structure of the electrode of the present invention included in the electric storage device may be an appropriate structure according to the type of the electric storage device, as described above. EXAMPLES
[0066] The materials used in the examples are as follows: <cnt> "LUCAN BT 1003M" (LG Chem, MWCNT) <Dispersant> Ethyl cellulose "ETHOCEL(R) STD-4 Industrial" (weight average molecular weight (Mw) approx. 44,000) Ethyl cellulose "ETHOCEL(R) STD-7 Industrial" (weight average molecular weight (Mw) approx. 55,000) Ethyl cellulose "ETHOCEL(R) STD-10 Industrial" (weight average molecular weight (Mw) approx. 77,000) Ethyl cellulose "ETHOCEL(R) STD-20 Industrial" (weight average molecular weight (Mw) approx. 105,000) Ethyl cellulose "ETHOCEL(R) STD-45 Industrial" (weight average molecular weight (Mw) approx. 135,000) Ethyl cellulose "ETHOCEL(R) STD-100 Industrial" (weight average molecular weight (Mw) approx. 180,000) Ethyl cellulose "ETHOCEL(R) STD-200 Industrial" (weight average molecular weight (Mw) approx. 188,000) Ethyl cellulose "ETHOCEL(R) STD-300 Industrial" The above ETHOCEL(R) series are manufactured by The Dow Chemical Company. Ethyl cellulose "Aqualon TM Ethylcellulose EC-N4 Ethyl cellulose "Aqualon TM ethylcellulose EC-N50 Ethyl cellulose "Aqualon TM ethylcellulose EC-N100 Ethyl cellulose "Aqualon TM ethylcellulose EC-N200 Ethyl cellulose "Aqualon TM ethylcellulose EC-N300 More Aqualon TM The ethylcellulose series is manufactured by Ashland. The ETHOCEL (registered trademark) series and Aqualon TM The cellulose ethers of the ethylcellulose series are all water-insoluble cellulose ethers in which some and / or all of the three hydroxyl groups of cellulose have been replaced with ethyl groups. Methylcellulose "Metolose (registered trademark) SM-4000" (Shin-Etsu Chemical Co., Ltd., water-soluble cellulose ether) Hydroxypropyl methylcellulose "Metolose (registered trademark) 60SH-4000" (Shin-Etsu Chemical Co., Ltd., water-soluble cellulose ether) Hydroxypropyl methylcellulose "Metolose (registered trademark) 90SH-4000" (Shin-Etsu Chemical Co., Ltd., water-soluble cellulose ether) Cellulose acetate "L-50" (Daicel, cellulose ester) <Binder> ·PVDF (Polyvinylidene fluoride) <Electrode active material> NCM523(LiNi 0.5 Co 0.2 Mn 0.3 O2) Tap density: 2.13g / cm 3 <Solvent> PM (Propylene glycol monomethyl ether) ·PMA (Propylene glycol monomethyl ether acetate) ·NMP (N-methyl-2-pyrrolidone)
[0067] (Examples 1 to 13: Production of CNT-containing powders 1 to 13) The weight ratio of CNT to each dispersant shown in Table 1 (CNT:dispersant) was adjusted to 80:20, and this was added to each solvent shown in Table 1 so that the solid content was 50 to 10% by weight, and kneaded using a planetary stirrer (temperature 30°C) to produce a paste-like kneaded product. The kneaded product was then dried to obtain CNT-containing powders 1 to 13.
[0068] (Comparative Examples 1 to 5: Production of CNT-Containing Powders 14 to 18) CNT-containing powders 14 to 18 were obtained in the same manner as in Example 1, except that the dispersants and solvents shown in Table 1 were used.
[0069] (Comparative Example 6: Production of CNT dispersion) Using CNTs and the dispersant and solvent shown in Table 1, a CNT dispersion (CNT concentration 0.1 wt%, CNT:dispersant=100:300) was obtained according to the conditions of Example 1 of WO 2017 / 188175.
[0070] [Table 1]
[0071] (Examples 14 to 26: Production of electrode mixture pastes 1 to 13) The CNT-containing powders 1 to 13 obtained in Examples 1 to 13 were kneaded together with NCM523 and PVDF in NMP using a planetary stirrer to prepare electrode mixture pastes 1 to 13 (solid weight composition NCM523:CNT:dispersant:PVDF=97.50:0.50:0.125:1.875). Note that the dispersant in the weight composition is derived from the CNT-containing powder. Table 2 shows the type of each component used and the solid content concentration during kneading.
[0072] (Comparative Examples 7 to 11: Production of Electrode Mixture Pastes 14 to 18) Electrode mixture pastes 14 to 18 were prepared in the same manner as in Example 14, except that CNT-containing powders 14 to 18 obtained in Comparative Examples 1 to 5 were used. Table 2 shows the type of each component used and the solid content concentration during kneading.
[0073] (Comparative Example 12: Production of electrode mixture paste 19) The CNT dispersion obtained in Comparative Example 6 was mixed with NCM523 and PVDF, concentrated to a solid content concentration of 57.5% by weight, and then kneaded using a planetary stirrer to prepare an electrode mixture paste 19 (solid content weight composition NCM523:CNT:dispersant:PVDF=97.50:0.50:1.50:0.50). Note that the dispersant in the weight composition is derived from the CNT dispersion.
[0074] [Table 2]
[0075] <Test Example 1: Surface resistivity and film thickness> The surface resistivity and film thickness of the electrodes prepared using the obtained electrode mixture pastes 1 to 19 were evaluated as follows. Surface resistivity of the electrode The surface resistivity of the electrode mixture layer (hereinafter referred to as electrode) formed by applying the electrode mixture pastes 1 to 19 to a PET sheet material to a thickness of 0.05 mm was measured using a low-resistance resistivity meter "Loresta (registered trademark)-GX MCP-T700" (manufactured by Nitto Seiko Analytech Co., Ltd.). The drying conditions (temperature, time) during electrode preparation are as shown in Table 2. Electrode thickness The thickness of the electrode mixture layer was measured using a high-precision Digimatic Micrometer "MDH-25MB" (manufactured by Mitutoyo Corporation). Five evaluation electrodes were prepared from one electrode mixture paste, and the volume resistivity was calculated from the average surface resistivity and the average film thickness. The results are shown in Table 2.
[0076] (Evaluation: Evaluation of volume resistivity) Anything under 100 Ω·cm (1.00E+02 Ω·cm) is acceptable. Anything over 100 Ω·cm (1.00E+02 Ω·cm) is a failure.
[0077] From the results shown in Table 2, all of the electrodes fabricated using the electrode mixture pastes 1 to 13 obtained in Examples 14 to 26 had low volume resistivity and excellent electrical conductivity. In contrast to this, the electrodes produced using the electrode mixture pastes 14 to 19 obtained in Comparative Examples 7 to 12 all had high volume resistivities.
[0078] <Test Example 2: Observation of surface condition> The surface condition of each electrode was observed using a scanning electron microscope. FIG. 1 shows an electron microscope image (a) (×5,000 magnification) of the surface of an electrode prepared using the electrode mixture paste 1 obtained in Example 14, and an enlarged electron microscope image (b) (×50,000 magnification) of the same. FIG. 2 shows an electron microscope image (a) (×5,000 magnification) of the surface of an electrode prepared using the electrode mixture paste 19 obtained in Comparative Example 12, and an enlarged electron microscope image (b) (×50,000 magnification) of the same.
[0079] As shown in FIG. 1(a), in the electrode prepared using the electrode mixture paste 1 obtained in Example 14, no aggregation of CNTs was observed on the surface of the active material. Further enlargement of the electrode surface as shown in FIG. 1(b) confirmed that the surface of the active material was uniformly covered with CNTs. On the other hand, as shown in FIG. 2(a), in the electrode produced using the electrode mixture paste 19 obtained in Comparative Example 12, multiple aggregated lumps of CNTs were observed on the surface. Furthermore, when the electrode surface was further enlarged as shown in FIG. 2(b), it was confirmed that the surface of the active material was not covered with CNTs, and there were large exposed areas, indicating that the CNTs were unevenly distributed.
[0080] From the above results, it can be seen that the CNT-containing powder for electrodes of the present invention has excellent dispersibility in electrodes for electricity storage devices, and therefore electrodes for electricity storage devices obtained using electrode composites or electrode mixture pastes containing the CNT-containing powder for electrodes of the present invention have low volume resistivity and excellent conductivity.< / cnt>
Claims
1. Carbon nanotubes (CNTs) Ethyl cellulose as a dispersant A CNT-containing powder for an electrode of an electricity storage device, comprising:
2. The CNT-containing powder for an electrode of an electricity storage device according to claim 1 , wherein the dispersant is attached to a surface of the CNT.
3. 2. The CNT-containing powder for an electrode of an electricity storage device according to claim 1, wherein a weight ratio of the content of the CNT to the content of the dispersant (CNT:dispersant) is 33:67 to 99:
1.
4. 4. An electrode composite for an electricity storage device, comprising the CNT-containing powder for an electrode according to claim 1 and an inorganic compound, wherein the inorganic compound is an electrode active material and / or a solid electrolyte.
5. An electrode mixture paste for an electricity storage device, comprising the CNT-containing powder for an electrode of an electricity storage device according to any one of claims 1 to 3, an electrode active material, a binder, and a solvent.
6. An electrode for an electricity storage device, comprising an electrode mixture layer formed using the electrode mixture paste for an electricity storage device according to claim 5.
7. An electricity storage device comprising an electrode mixture layer formed using the electrode mixture paste for an electricity storage device according to claim 5.
8. A method for producing the CNT-containing powder for an electrode of an electricity storage device according to any one of claims 1 to 3, comprising: A method comprising kneading CNTs, a dispersant and a solvent to prepare a paste-like kneaded mixture, and then drying the kneaded mixture to obtain a CNT-containing powder.
9. The method according to claim 8, wherein the solvent is at least one selected from the group consisting of alcohol-based solvents, amine-based solvents, ether-based solvents, glycol ester-based solvents and ketone-based solvents.
Citation Information
Patent Citations
Fine carbon fiber aggregate for redispersion and method for producing the same
JP2008274502A
Carbon nanotube dispersion, method for producing same, and conductive molded body
WO2017188175A1